Antecedents and correlates of blood concentrations of neurotrophic growth factors in very preterm newborns. (June 2017) - Leviton, Alan; Allred, Elizabeth N.; Yamamoto, Hidemi; Fichorova, Raina N.; Kuban, Karl; O'Shea, T. Michael; Dammann, Olaf; ,
Highlights: Growth factors have the potential to minimize brain and retinal damage in very preterm newborns. Previously, pregnancy correlates of high concentrations in the very preterm newborn were unknown. We found that concentrations vary with indications for delivery, and fetal growth restriction. Previously, inflammation correlates of high concentrations in very preterms were unknown. We found that concentrations vary with systemic inflammation. Abstract: Aim: To identify the antecedents and very early correlates of low concentrations of neurotrophic growth factors in the blood of extremely preterm newborns during the first postnatal month. Methods: Using an immunobead assay, we measured the concentrations of neurotrophin 4 (NT4), brain-derived neurotrophic factor (BDNF), and basic fibroblast growth factor (bFGF) in blood spots collected on postnatal days 1 (N = 1062), 7 (N = 1087), 14 (N = 989), 21 (N = 940) and 28 (N = 880) from infants born before the 28th week of gestation. We then sought the correlates of measurements in the top and bottom quartiles for gestational age and day the specimen was collected. Results: The concentrations of 2 neurotrophic proteins, NT4 and BDNF, were low among children delivered for medical (maternal or fetal) indications, and among those who were growth restricted. Children who had top quartile concentrations of NT4, BDNF, and bFGF tended to have elevated concentrations of inflammation-related proteins that day. This pattern persisted for much of the first postnatal month. Conclusions: Delivery for medical indications and fetal growth restriction are associated with a relative paucity of NT4 and BDNF concentrations during the first 24 h after very preterm birth. Elevated blood concentrations of NT4, BDNF, and bFGF tended to co-occur with indicators of systemic inflammation on the same day.